Proteolysis of lactoferrin and β-casein in complex coacervate and uncomplexed forms during in vitro infant gastrointestinal digestion - Jasper M. van der Schaaf; David A. Goulding; Jonathan O'Regan; Michael Affolter; James A. O'Mahony; Alan L. Kelly (Journal of Functional Foods, 2024)
Lactoferrin is of interest for infant nutrition due to its roles in supporting gastrointestinal development. When supplemented orally, digestive exposure may reduce the availability and biofunctionality of the protein and its derived peptides. The aim of this study was to evaluate the proteolysis of bovine lactoferrin and β-casein coacervates following infant in vitro digestion. Coacervation of β-casein with lactoferrin showed a protective function against peptic proteolysis, increasing the levels of intact β-casein and lactoferrin during gastric digestion, while the uncomplexed β-casein was readily proteolyzed. The coacervate was shown to protect the C-terminal of β-casein against gastric proteolysis. This resulted in altered peptide profiles in the gastric and intestinal phases, requiring additional research to ascertain potential implications for biological activity. This study demonstrates the impact of protein–protein interactions on proteolysis during digestion, which may delay proteolysis and possibly protect the bioactive properties of the proteins.